Comparison between Different Optical Configurations of Active-FRAME Setup in Multispectral Imaging of Flames - Chorey, Devashish; Boggavarapu, Prasad; Deshmukh, Devendra; Rayavarapu, Ravikrishna; Mishra, Yogeshwar Nath (Photonics, 2024)
Snapshot multispectral imaging of chemical species in the flame is essential for improved understanding of the combustion process. In this article, we investigate the different configurations of a structured laser sheet-based multispectral imaging approach called the Frequency Recognition Algorithm for Multiple Exposures (FRAME). Using FRAME, a snapshot of Laser-Induced Fluorescence (LIF) of Polycyclic Aromatic Hydrocarbons (PAH) excited by 283.5 nm laser and Laser-Induced Incandescence (LII) of soot particles excited by 532 nm laser are acquired simultaneously on a single FRAME image. A laminar diffusion flame of acetylene produced by a Gülder burner is used for the experiments. The standard FRAME approach is based on creating two spatially modulated laser sheets and arranging them in a cross-patterned configuration (X). However, the effect of using different configurations (angles) of the two laser sheets on the multispectral planar imaging of the flame has not yet been studied. Therefore, we have compared the FRAME approach in four different configurations while keeping the same flame conditions. First, we have compared the relation between laser fluence and LII signals with and without spatial modulation of the 532 nm laser sheet and found that both detections follow the same curve. When comparing the maps of flame species reconstructed from the standard FRAME configuration and other configurations, there are some dissimilarities. These differences are attributed to minor changes in the imaging plane, optical alignment, laser path length, different modulation frequencies of the laser sheet, laser extinction, laser fluence, etc.
CRIS-Team Scopus Importer:2025-02-04
Keywords: combustion diagnostics; laser-induced fluorescence; laser-induced incandescence; multispectral imaging; simultaneous imaging; structured illumination